Hubungan Resiko Posisi Kerja Duduk Terhadap Keluhan Musculoskeletal Disorders (MSD) Pada Pegawai Pemerintah Kabupaten Malang - Lubis, Zidni Imanurrohmah; Yulianti, Atika; Nisa, Fiqih Khoirun; Ayulianda, Sielma Ajeng (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 7 No 1 (2021): Volume 7 N0 1 June 2021DO - 10.24843/JEI.2021.v07.i01.p08, 2021)
In the work process, the work position is maintained for a long time and complaints of pain due to this position often appear in the soft tissues of the body and joints, from mild to severe due to prolonged loading. This condition is called Musculoskeletal Disorder (MSD). The prevalence of MSD disorders is reported to continue to increase in young productive age. Therefore, the risk factors need to be known so that the relationship between the risk of a sitting position with MSD complaints on office employees, namely Malang Regency government employees can also be known. This study had an observational analytic design with cross sectional method. A total of 71 respondents were obtained using random and purposive sampling. The results of the data normality test showed that the data were not normally distributed. From the results of the correlation test, the value of p> 0.05 (p = 0.644) was obtained, so that H0 was accepted. So the conclusion of this study is that there is no relationship between sitting work position and complaints of musculoskeletal disorders (MSD) in Malang Regency Government officials and the factors that affect MSD need to be further investigated.